Stages of the Evolution of Sino-American Competition in Latin America: An Analytical Study - shaker, Mohammed; Muthanna F. Merie (Tikrit Journal For Political Science, 2024)
The Latin American region is considered one of the strategically important areas globally. Consequently، international powers strive to compete in the region، seeking to gain and expand their influence. One of the most significant competitors in the region is China، which historically has had trade relations with Latin American countries since the latter half of the 16th century. After World War II and China's emergence as a major power، it began to broaden its influence in Latin America. The second stage، from 2001 to 2009، marked the actual establishment of Chinese influence in the region. Due to the region's importance to the United States and its perception of the looming Chinese threat in its backyard، the U.S. began attempting to reclaim its traditional influence in the area. This competition between the two powers intensified due to the geopolitical significance of the region.